German aid for trade: past experience, lessons learnt, and the way forward - Petra Voionmaa; Michael Brüntrup (Deutsches Institut für Entwicklungspolitik (DIE), 2009)
The Aid for Trade (AfT) initiative was launched within the WTO with the aim of helping developing countries to reduce poverty by getting more engaged in trade. It recognises that market access alone is of little use for many poor countries. Instead, it draws attention to a number of obstacles that have prevented many countries from reaping the benefits available in a globalised world as well as to the risks arising from such increased openness.This study presents the results of a research project commissioned by the German Federal Ministry for Economic Cooperation and Development. Its aim is to provide input for an informed discussion on how Germany can best contribute to the AfT initiative by optimising both the quantity and quality of its trade-related assistance. After outlining the theoretical debate behind trade and development, the study describes the process behind the AfT initiative as well as the challenges involved in putting it into practice. An analysis of international and – in more detail – German AfT prepares the ground for a discussion on how Germany should shape its AfT portfolio in accordance with its assumed comparative advantages.
Keywords: 330